Encyclopedia of mobile phone behavior: [Bd. 1-3] - Yan, Zheng (Information Science Reference, 2015)
"This book is an authoritative source for scholarly research on the use of mobile phones and how these devices are revolutionizing the way individuals learn, work, and interact with one another"--
Includes bibliographical references and index ; Enth. alle Bd. der Druckausg